ATTRACTORS OF THE DEGENERATING EVOLUTIONARY EQUATIONS - Tsutsulian, A. V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2000)
This article proves the existence of semigroup attractors generated by mixed problems for degenerate second-order evolution equations, where degeneration can occur either on the entire boundary or on a part of it. The compactness of the attractors in the space L2 is established, and a Lyapunov function is constructed to elucidate their structure.
Keywords: attractors; degenerate second-order evolution equations